Polyfunctionality of CD4+ T lymphocytes in buffaloes and cattle: comparative antigen-specific cytokine responses in bovine tuberculosis infection - Flores-Villalva, Susana; De Matteis, Giovanna; Grandoni, Francesco; Scatà, Maria Carmela; Donniacuo, Anna; Schiavo, Lorena; Franzoni, Giulia; Mazzone, Piera; Elnaggar, Mahmoud; De Carlo, Esterina; Galiero, Giorgio; Davis, William C.; et al. (Frontiers in Immunology, 2025)
IntroductionBovine tuberculosis (BTB), caused by Mycobacterium bovis, is a chronic infectious disease of major veterinary and public health concern. It affects a broad range of domestic and wild animals, including water buffalo, and poses a risk to humans due to its zoonotic nature. The economic consequences of BTB, arising from production losses and trade restrictions, further underline its global importance. While cattle immune responses to BTB are well characterized, the immune mechanisms in buffalo remain poorly understood, despite their increasing role as livestock in endemic regions. Given that buffaloes and cattle, although closely related, display notable immunological differences, comparative studies are essential. This study aimed to investigate and compare antigen-specific cytokine responses in CD4+ T lymphocytes from buffaloes and cattle exposed to or infected with M. bovis.MethodsA multicolor flow cytometry assay was established to enable high-resolution analysis of cytokine-expressing CD4+ T cells. Blood samples were obtained from 35 buffaloes (17 IGRA-positive from BTB outbreak farms and 18 IGRA-negative, including animals from both outbreak and Officially Tuberculosis-Free [OTF] herds) and 10 cattle (6 IGRA-positive from a BTB outbreak farm and 4 IGRA-negative from an OTF herd). Following six hours of in vitro stimulation with PPD-B or PBS, intracellular cytokine staining was performed. This approach allowed simultaneous quantification of single and polyfunctional CD4+ T cell subsets producing IFN-γ, TNF-α, and IL-17A. Data were analyzed using factor analysis of mixed data (FAMD) to explore species- and infection-related immune response patterns.ResultsThe multicolor flow cytometry approach successfully identified distinct cytokine-producing CD4⁺ T cell populations in both species. Overlapping immune profiles were observed between buffaloes and cattle; however, specific subsets—including IL-17A+, IFN-γ+IL-17A+, and TNF-α+IL-17A+ cells—contributed to interspecies differences. Importantly, the frequency of IFN-γ+ and TNF-α+ producing CD4+ T cells correlated with IGRA test status, enabling discrimination between infected/exposed and non-infected animals. These results demonstrate the ability of cytokine expression patterns to reflect both infection status and host species.DiscussionThe findings indicate that buffaloes and cattle share broadly similar antigen-specific cytokine responses, although subtle differences in CD4⁺ T cell subsets exist. The study highlights the value of multicolor flow cytometry as a high-resolution tool for dissecting immune responses in veterinary immunology. These insights enhance understanding of buffalo immune mechanisms against BTB and may contribute to improved disease control strategies.